2019
DOI: 10.1002/anie.201908743
|View full text |Cite
|
Sign up to set email alerts
|

A Butterfly‐Inspired Hierarchical Light‐Trapping Structure towards a High‐Performance Polarization‐Sensitive Perovskite Photodetector

Abstract: Extensive applications for photodetectors have led to demand for high‐responsivity polarization‐sensitive light detection. Inspired by the elaborate architecture of butterfly Papilio paris, a 1D nanograting bonded porous 2D photonic crystal perovskite photodetector (G‐PC‐PD) using a commercial DVD master and 2D crystalline colloidal arrays template was fabricated. The coupling effect from grating diffraction and reflection of the PC stopband renders the enhanced light harvesting of G‐PC‐PD. The porous scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 58 publications
3
77
0
Order By: Relevance
“…Worldwide researchers' attention has been paid on perovskites to producing broad applications of light‐emitting diodes (LEDs), optically pumped lasers, pholoelectrochemical (PEC) cells, and photodetectors 6. The direct bandgap nature, high light absorption ability, and wide‐range light absorption of perovskites make them suitable candidates for photodetectors with broadband photoresponse 8. The short conduction pathway for photogenerated charge carriers ensures the related photoelectric devices with fast response speed.…”
Section: Materials For Heterojunction Uv Pdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide researchers' attention has been paid on perovskites to producing broad applications of light‐emitting diodes (LEDs), optically pumped lasers, pholoelectrochemical (PEC) cells, and photodetectors 6. The direct bandgap nature, high light absorption ability, and wide‐range light absorption of perovskites make them suitable candidates for photodetectors with broadband photoresponse 8. The short conduction pathway for photogenerated charge carriers ensures the related photoelectric devices with fast response speed.…”
Section: Materials For Heterojunction Uv Pdsmentioning
confidence: 99%
“…Presently, the researches on perovskites,6–11 graphene,12 and other materials2,13–16 are emerging in an endless stream and these materials with excellent properties can be used for heterojunction UV PDs. Perovskites are a good choice for optoelectronic devices because of their tunable bandgaps, large extinction coefficient, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] Moreover, the periodic pore structure of the inverse opal particles generated brilliant structural colors which enabled sensing and self-reporting of the adsorption state, as manifested by the reflection peak shift of the MIPIOPs. [37][38][39][40][41] It was demonstrated that the hierarchically structured MIPIOPs, integrated with the herringbone mixer, realized efficient cleaning of multiple targets both in water and in serum. Therefore, this novel platform offers great potential in clinical blood purification and artificial kidney construction.…”
Section: Doi: 101002/adma202005394mentioning
confidence: 99%
“…Inspired by the hierarchical structures of the butterfly's black wings, hierarchical perovskite films, whose bottom was a porous 2D photonic crystal (PC) structure and top was a 1D nanograting structure, were fabricated by using spincoating with the monolayer polystyrene (PS) spheres and nanoimprinting with a DVD as presented in Figure 7g). [ 104 ] Optical characterizations and calculation of the field intensity distributions were performed, showing the unique structures endow the perovskite thin films with higher crystallinity and stronger light‐harvesting (Figure 7h). Therefore, the photodetector with 2D PC structures and 1D nanogratings exhibited high white‐light responsivity of 12.67 A W −1 and detectivity of 3.22 × 10 13 Jones, which is 6–7 times higher than that with planar perovskite films (Figure 7i).…”
Section: Patterned Perovskites For Optoelectronic Applicationsmentioning
confidence: 99%